Linguistic politeness between Filipino professors and American students in the University of the Philippines Los Banos during academic consultation sessions - Labor, Jonalou S. (UP Los Baños Journal, 2009)
Linguistics politeness is a form of linguistic behavior that operates outside of the realm of politic behavior. In this study, texts produced from sixteen academic consultation sessions were transcribed, tabulated, and analyzed using discourse analysis in order to find out if linguistic politeness were used by Filipino professors and American students in the University of the Philippines Los Banos.